A study on the body composition and physical characteristics of top-level high school female handball players - Okano, K.; Kuki, S.; Yoshida, T.; Tanigawa, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
The present study was conducted to clarify the body composition and physical characteristics of elite high school female handball players, and to compare those variables between starters and nonstarters in a team. Seventeen elite high school female handball players without a goalkeeper volunteered for the study. Body composition, height and body mass were measured. Physical characteristics investigated included grip strength, 20-m sprint time, pro-agility time, jump ability, sitting handball throw and Yo-Yo intermitted test. As jump ability parameters, data on counter movement jump (CMJ) height, rebound jump index (RJ index) and standing broad jump distance were collected. The characteristics of the study subjects overall were as follows: height 159.3±5.9 cm, body mass 55.0±4.2 kg, grip strength 29.4±3.7 kg, 20-m sprint time 3.42±0.12 s, pro-agility time 5.13±0.18 s, CMJ height 31.0±3.7 cm, RJ index 1.547±0.222, standing broad jump distance 1.97±0.16, handball throw 15.8±2.0 m, yo-yo intermitted test 3075±547.3 m. Comparison of the 2 groups showed that starters were significantly superior to nonstarters in terms of the RJ index and yo-yo intermitted test. However, the 20-m sprint time and pro-agility time of nonstarters were significantly higher than those of starters. These data would be valuable for identifying talented female handball players.